Cyclic and Explosive Evaluation of New Proposed Steel Joint - Iman Faridmehr; Yusof Ahmad; Mahmood Md. Tahir; Mohd Hanim Osman (Advances in Civil Engineering)
The behaviour of a novel steel beam-to-column connection, the saddlebag, subjected to cyclic and progressive collapse, was evaluated in this paper. The cyclic behaviour considered the interstory drift angle and flexural strength in accordance with 2010 AISC Seismic Provisions, while progressive collapse assessment was evaluated through the plastic hinge rotation angle based on acceptance criteria provided in the UFC 4-023-03 guideline. From the cyclic test, one complete cycle of an interstory drift angle of 0.06 rad was satisfied for the saddlebag connection, which is an indication of the effectiveness in accordance with 2010 AISC Seismic Provisions. Besides, the new proposed connection developed adequate catenary action, which is a fundamental criterion to resist against progressive collapse. The resulting fuller hysteretic loops with large energy dissipation capacity in the proposed saddlebag connection guarantee its ability to address the inelastic deformation demands in earthquake conditions.